Possibilities and importance of applying learning through research with children in the community - pre-school teacher’s perspective - Stepić, Gordana M.; Dedaj, Marta D.; Džaić, Biljana M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
Starting from the perception of a child as a researcher from the very birth, the research nature of his/her learning, the importance of the community for the learning and development of a preschool child, the goal of this research is to consider pre-school teachers’ perspective and learning opportunities through research with children in the community. The research used the method of theoretical analysis and the descriptive method and two research techniques: scaling and content analysis of pedagogical documentation. The following research instruments were used: an assessment scale and a protocol for the analysis of pedagogical documentation. Twenty pre-school teachers participated in the research. The content sample consisted of nine stories on topics/projects. The research indicates that learning through research with children in the community is integrated into the educational process, that pre-school teachers recognize and know the value of this approach and that they mostly have the support of the community. The importance is also highlighted of recognizing challenges through reviewing practice and dealing with them in order to work continuously on improving learning through research with children in the community.